2017
DOI: 10.1016/j.jneumeth.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of administration method, animal weight and age on the intranasal delivery of drugs to the brain

Abstract: Background The intranasal route of administration has proven to be an effective method for bypassing the blood brain barrier and avoiding first pass hepatic metabolism when targeting drugs to the brain. Most small molecules gain rapid access to CNS parenchyma when administered intranasally. However, bioavailability is affected by various factors ranging from the molecular weight of the drug to the mode of intranasal delivery. Comparison with Existing Methods We examined the effects of animal posture, intrana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The rats were kept in the supine position for 2 min after administration of the dose. All experiments were carried out at 20 ± 5 °C (Krishnan 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The rats were kept in the supine position for 2 min after administration of the dose. All experiments were carried out at 20 ± 5 °C (Krishnan 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Possibly, this may hint that the distribution to the CNS does not include drainage to the CSF or is rapidly cleared from the CSF [47][48][49]. Further studies are necessary to elucidate the involvement of the CSF, but also of the glymphatic system [50][51][52][53]. It should be noted that CSF samples were also analyzed from the mice in study 3 by ELISA, but no significant amounts of 11C7, IC, or 11C7 scFv could be determined.…”
Section: Reduced Elimination From Cns Of Nogo-a-binding Iggmentioning
confidence: 99%
“…Even in the same animal model, intranasal injection shows different delivery efficacy according to animal age and weight. Krishnan et al injected the drug radiolabeled pralidoxime into the nasal cavity of model animals, which showed that compared with younger animals with lower body weight, older animals with higher body weight required a higher dose to reach the same drug concentration in the whole brain [ 77 ]. This suggested that the distribution of intranasally administered stem cells might be affected by the age and body weight of model animals.…”
Section: Limitations Of Intranasal Stem Cell Therapymentioning
confidence: 99%